The US and Ireland approach to sentencing in cartel cases: The Citroen case - Paul K. Gorecki; Sarah Maxwell (The Economic and Social Research Institute (ESRI), 2013)
Developing a coherent evidence based methodology for determining sanctions in cartel cases is vitally important for robust cartel enforcement in Ireland. This methodology should take into account aggravating/mitigating factors for individuals as well as culpability indicators for firms, while at the same time taking cognisance of the economic damage caused by cartels to consumers. Irish Courts, despite presiding over 33 convictions on indictment for cartel offences stretching back over six years have, as yet, to develop such a methodology. While the Duffy judgment, the only reported judgment on sentencing of a cartel member, the Court provides some guidance on sentencing. It states, for example, that cartels are bad and pernicious and that jail sentences are to be expected in future cartel cases. This is not a coherent sentencing methodology. The Sentencing Guidelines, developed by the US Sentencing Commission, provide such a methodology, while at the same allowing for judicial discretion. Applying that methodology to the facts of the Citroen cartel case in Ireland, in which 14 individuals and firms were convicted on indictment, suggests that the current approach to sentencing in Ireland by the Courts results in fines and jail sentences that are too low. This encourages rather than discourages cartel activity which raises prices for consumers and thus damages consumer welfare.
Keywords: 330